PENGARUH ORIENTASI KONSUMEN, PESAING DAN LINGKUNGAN EKSTERNAL TERHADAP KINERJA PEMASARAN UKM DI KOTA BANJARBARU DAN BANJARMASIN - Ni Nyoman Suarniki (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, The purpose of the research is to uncover the influence of consumer’s orientation, competitors and external environment toward the performance of UMKM (Community’s Small and Intermediate Business) in Banjarbaru both simultaneously and partial. This research was conducted with the object of SMEs (small and micro enterprises) in the city of Banjarmasin and Banjarbaru. This research finds that the external environmental variable possesses t quantification as many as 7.933 compared to t table of 2.677 which results t quantification > t table, hence concludes that consumer’s orientation variable has significant influence on the performance of UKM in Banjarmasin and Banjarbaru. The consumer’s orientation variable has t quantification of 1.560 compared to t table of 2.677 which results t quantification > t table, hence concludes that consumer’s orientation variable possesses insignificant influence on the performance of UKM’s marketing in Banjarmasin and Banjarbaru. Whereas competitors variable has t quantifications of 4.208 compared to t table of 2.677 which results t quantification > t table, hence concludes that competitors variable possesses significant influence on UKM’s marketing in Banjarmasin and Banjarbaru. The most dominant variable on the performance of UKM’s marketing performance in Banjarmasin and Banjarbaru is external environment variable because having the biggest t quantification of 7.933.